2013
DOI: 10.1002/rog.20017
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Barents Sea in the Arctic Climate System

Abstract: Present global warming is amplified in the Arctic and accompanied by unprecedented sea ice decline. Located along the main pathway of Atlantic Water entering the Arctic, the Barents Sea is the site of coupled feedback processes that are important for creating variability in the entire Arctic air‐ice‐ocean system. As warm Atlantic Water flows through the Barents Sea, it loses heat to the Arctic atmosphere. Warm periods, like today, are associated with high northward heat transport, reduced Arctic sea ice cover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
382
0
14

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(433 citation statements)
references
References 219 publications
(426 reference statements)
37
382
0
14
Order By: Relevance
“…4a and b). It is well known that winter sea ice variability in the BS dominates that in the Arctic Ocean (e.g., Smedsrud et al, 2013), which is consistent with our results. At a lag of 9 months (Fig.…”
Section: Possible Mechanisms For Prediction Skillsupporting
confidence: 93%
“…4a and b). It is well known that winter sea ice variability in the BS dominates that in the Arctic Ocean (e.g., Smedsrud et al, 2013), which is consistent with our results. At a lag of 9 months (Fig.…”
Section: Possible Mechanisms For Prediction Skillsupporting
confidence: 93%
“…3B and 5A and Fig. S7 A and B), and the observed increase in HT BSO is also found as a prime driver for the recent observed sea ice decline in Barents Sea (46,47). Hence, at low frequency, the March Barents Sea SIE anomaly can be taken as a proxy for the HT BSO anomaly (Methods).…”
Section: Implications For Observed Summer Arctic Sea Ice Declinementioning
confidence: 84%
“…6c). Previous authors have suggested that the link between Arctic sea ice and the NAO is nonstationary (e.g., Smedsrud et al 2013); however, particularly given the length of the available observational record, the temporally limited correlation between PC1 and the NAO shown in Fig. 6b should also be considered in the context of the cautionary note of Wunsch (1999), where it was emphasized that two uncorrelated stochastic time series may exhibit isolated periods of common low-frequency variability simply by chance.…”
Section: Discussionmentioning
confidence: 99%